Sulfur origin and flux variations in fumarolic fluids of Vulcano Island, Italy - Inguaggiato, Salvatore; Liotta, Marcello; Rouwet, Dmitri; Tassi, Franco; Vita, Fabio; Schiavo, Benedetto; Ono, Shuhei; Keller, Nicole Simone (Frontiers in Earth Science, 2023)
A sharp increase in volatiles, especially SO2 fluxes from the solfataric plume and diffuse CO2 from the soils of the La Fossa crater area, started in June 2021, and subsequently from the Levante Bay area, suggests renewed unrest at Vulcano Island, Italy. This event has encouraged monitoring activities and stimulated new research activities aimed at understanding the recent evolution of the volcanic system. In this study, the chemical and isotopic composition of fumaroles, thermal waters, and soil gases from the main degassing areas of Vulcano Island with a special focus on sulfur isotopes, are used to investigate the fluid transfer mechanism inside the volcano. Sulfur is one of the most abundant volatile elements present in magmas and volcanic fluids from the La Fossa crater, where it mostly occurs as SO2 and H2S at variable relative concentrations depending on oxygen fugacity and temperature. The isotope composition and the chemical ratio of sulfur species depict a complex hydrothermal-magmatic system. In addition, we utilize the installed SO2 monitoring network that measures the total outgassing of SO2 with the UV-scanning DOAS technique. The SO2 fluxes from the La Fossa crater fumaroles, coupled with the SO2/CO2 and SO2/H2O ratios, were measured to evaluate the total mass of fluids emitted by the shallow plumbing system and its relationship with the status of volcanic activity. Combining the whole chemical composition of fumaroles analyzed with a discrete, direct sampling of high-temperature fumaroles located on the crater summit, the output of discharged water vapor has been estimated (5,768 t·d−1). On the basis of the water output, we estimated the total thermal energy dissipated by the crater during the last enhanced degassing activity (167 MW). This strong and sharp increase in energy observed during the current crisis confirms the long-growing trend in terms of mass and energy recorded in recent decades, which has brought the surface system of Vulcano Island to a critical level that has never been recorded since the last eruptive event of 1888–91.